Slow depolarizing electrical stimuli reveal differential time courses of nociceptor recovery after prolonged topical capsaicin in human skin - Tumbala Gutti, Divya; Carr, Richard; Schmelz, Martin; Rukwied, Roman (European journal of pain, 2025)
Background We examined de-functionalization and temporal functional recovery of C-nociceptor evoked pain after topical 8% capsaicin applied for 4 consecutive days. Methods Capsaicin and placebo patches were applied to human forearm skin (n = 14). Cold, warmth and heat pain thresholds, pain NRS to electrical and thermal (48°C, 5 s) stimuli and axon reflex flare were recorded weekly for 49 days. Mechanical and heat sensitive (‘polymodal’) nociceptors were activated by single electrical half-period sinusoidal pulses (0.5 s, 1 Hz). Mechanical and heat insensitive (‘silent’) nociceptors were activated by 4 Hz sinusoidal stimuli. Results Capsaicin abolished heat pain. Sensation to electrical sinusoidal stimulation was reduced but never abolished during the treatment. Pain to electrical 1 Hz ‘polymodal’ nociceptor stimulation took longer to recover than pain ratings to 4 Hz 2.5 s sinusoidal stimulation activating ‘polymodal’ and ‘silent’ nociceptors (35 vs. 21 days). Heat pain was indifferent to placebo from day 21-49. Axon reflex flare was abolished during capsaicin and only recovered to 50% even after 49 days. Conclusions Capsaicin abolishes heat transduction at terminal nociceptive endings, whereas small-diameter axons sensitive to sinusoidal electrical stimulation can still be activated. 1 Hz depolarizing stimuli evoke burst discharges, as demonstrated before, and recover slower after capsaicin than single pulses induced by 4 Hz. The difference in recovery suggests differential time course of functional regeneration for C-nociceptor sub-types after capsaicin. All sensations recovered completely within 7 weeks in healthy subjects. Our findings contrast analgesia lasting for months in spontaneous neuropathic pain patients treated with 8% capsaicin. Significance Sinusoidal electrical stimulation can still activate small diameter axons desensitized to heat after 4 consecutive days of topical 8% capsaicin application and reveals differential temporal functional regeneration of C-nociceptor sub-types. Electrical sinusoidal stimulation may detect such axons that no longer respond to heat stimuli in neuropathic skin.